A room-temperature heptazine core discotic liquid crystal. Issue 14 (8th December 2017) - Mir Sayed, Sayed; Deng, Lin-Lin; Lin, Bao-Ping; Yang, Hong
ABSTRACT: Heptazine is the fundamental structural and functional unit of graphitic carbon nitrides and has a π-conjugated planar symmetry with semiconducting properties. Molecular self-assembly is one of the key factors to drive the electronic behaviour of π-conjugated organic molecules. To enhance the semiconductivity, heptazine is decorated at its active sites with 2, 3, 5-tris(dodecyloxy)aniline to get well-organised columnar packing. A novel heptazine-core room-temperature discotic liquid crystal (HDLC ) with hexagonal columnar geometry is discovered. The molecular structure and mesomorphic properties ofHDLC are investigated by 1 H-NMR, 13 C-NMR, IR, polarised optical microscopy, differential scanning calorimetry and X-ray diffraction. Photophysical and electrochemical properties ofHDLC are studied by UV–vis/fluorescence spectroscopy and cyclic voltammetry (CV), respectively. The energy band gap ofHDLC estimated from CV at room temperature is 1.63 eV, which is much narrower than the previously reported band gap for heptazine derivatives. This decrease in the energy band can be attributed to the particular designing ofHDLC for columnar packing. As a columnar liquid crystal providing a smooth path to the charge transport, HDLC with such a narrow energy band gap may find applications in organic electronics. Graphical Abstract: